2021
DOI: 10.1007/s11845-021-02752-7
|View full text |Cite
|
Sign up to set email alerts
|

Emergency medical admissions and COVID-19: impact on 30-day mortality and hospital length of stay

Abstract: Background The COVID-19 pandemic has put considerable strain on healthcare systems. Aim To investigate the effect of the COVID-19 pandemic on 30-day in-hospital mortality, length of stay (LOS) and resource utilization in acute medical care. Methods We compared emergency medical admissions to a single secondary care centre during 2020 to the preceding 18 years (2002–2019). We investigated 30-day in-hospital mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Total hospitalization costs in this study were similar to others 35 but were significantly higher among recipients of high-versus low-dose anticoagulation. Similarly, overall ICU utilization was in line with that reported in other studies of patients with COVID-19, 32,33,39 but was twice as high among patients who received highversus low-dose anticoagulation, and consistent with another retrospective study reporting a three-fold increase in ICU admission. 30 Variations in HRU and costs across studies probably reflect differences in study time periods, geographic locations, and severity of illness indicators.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Total hospitalization costs in this study were similar to others 35 but were significantly higher among recipients of high-versus low-dose anticoagulation. Similarly, overall ICU utilization was in line with that reported in other studies of patients with COVID-19, 32,33,39 but was twice as high among patients who received highversus low-dose anticoagulation, and consistent with another retrospective study reporting a three-fold increase in ICU admission. 30 Variations in HRU and costs across studies probably reflect differences in study time periods, geographic locations, and severity of illness indicators.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, overall findings on hospital LOS, ICU utilization, and cost were in line with results from studies of patients with COVID-19 in which assessment was not based on anticoagulant dose. [32][33][34][35][37][38][39][40] Among all inpatients, median LOS was approximately two days shorter than that reported by others, 32,34,39,50 but after examining anticoagulant use, we found that LOS was about 3 days longer among patients receiving high-versus low-dose heparinoids. Total hospitalization costs in this study were similar to others 35 but were significantly higher among recipients of high-versus low-dose anticoagulation.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…It is important to note the backdrop of the COVID-19 pandemic in spring 2020 (many of the post-protocol cohort patients) placed a large burden on the healthcare system, resulting in worse outcomes and hospital quality measures, notably, increased mortality rates and longer hospitalizations. 29 , 30 The cause of this shortened length of stay is likely 3-fold. First, the protocol reduced the time to surgery which has been previously demonstrated to reduce overall length of stay and allow for more rapid rehabilitation and improvement in functional outcomes.…”
Section: Discussionmentioning
confidence: 99%